1996
DOI: 10.1172/jci118921
|View full text |Cite
|
Sign up to set email alerts
|

Selective expansion of specific T cell receptors in the inflamed colon of Crohn's disease.

Abstract: To identify disease-specific T cell changes that occur in Crohn's disease (CD), the T cell receptor BV repertoires of lamina propria lymphocytes (LPL) isolated from both the inflamed and "disease-inactive" colons of seven CD patients were compared by the quantitative PCR and DNA sequence analysis. It was observed that the BV repertoires of LPL isolated from the disease-active and disease-inactive parts of the colon from the same individual were very different. Furthermore, nearly all of the differences occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…In our experimental colitis model, when a single pure antigen (TNBS) was present on the intestinal mucosa, a shift in the TCR repertoire of proliferative T cells became evident. Guiwani-Akolkar et al [7]investigated the TCR Vβ repertoire of LPLs isolated from both inflamed and ‘disease-inactive’ colons of patients with Crohn’s disease, and nearly all of the differences occurred in CD4+ T cells and very few differences in CD8+ cells. Their results in a patient with Crohn’s disease were similar to ours in TNBS-induced colitis which indicates that analysis of the TCR Vβ repertoire of IBD needs to be performed at sites exhibiting peaked inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our experimental colitis model, when a single pure antigen (TNBS) was present on the intestinal mucosa, a shift in the TCR repertoire of proliferative T cells became evident. Guiwani-Akolkar et al [7]investigated the TCR Vβ repertoire of LPLs isolated from both inflamed and ‘disease-inactive’ colons of patients with Crohn’s disease, and nearly all of the differences occurred in CD4+ T cells and very few differences in CD8+ cells. Their results in a patient with Crohn’s disease were similar to ours in TNBS-induced colitis which indicates that analysis of the TCR Vβ repertoire of IBD needs to be performed at sites exhibiting peaked inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Such reports include reference to the therapeutic effect of anti-CD4 monoclonal antibody (mAb) [1], the remission of Crohn’s disease after human immunodeficiency virus infection [2], the increase in the percentage of CD4+CD45RO+ T cells (considered as memory T cells) in patient’s with Crohn’s disease [3], the increase in the number of CD4+ and CD8+ T cell subsets expressing T cell receptor (TCR) Vβ8 in mesenteric lymph nodes during Crohn’s disease [4], and the dominant expression of a CD4+ Vβ5.2/5.3 T cell clone derived from intestinal intraepithelial lymphocytes (IELs) [5]. There are few reports available on the involvement of CD8+ T cells in IBDs [6, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] In addition, the development of IBD is associated with the enhanced expression of cell adhesion molecules in the colonic mucosa of experimental animals and humans. 30,31) In order to elucidate the tissue specific contribution of adhesion molecules to T cell-mediated inflammation, parallel experiments were performed in the large intestine of Th1 and Th2 celltransferred mice by intrarectal administration of the relevant antigen.…”
Section: )mentioning
confidence: 99%
“…To decrease the possible effects during the cloning procedure, CDR3 analysis of bulk culture of lamina propria T cells without long-term culture with allogenic feeder cells was carried out, and oligoclonality was again noted in Crohn’s disease but not in ulcerative colitis or in normal subjects. Furthermore, Gulwani-Akolkar et al [24, 25]also demonstrated oligoclonally expanded CD4-positive T cells in Crohn’s disease. Vigorous investigation seeking a common T-cell clone has continued, and we have identified several consistent clones expanded in the skipped lesion of the same patient.…”
Section: T-cells In the Early Lesion Of Crohn’s Disease Expanded Oligmentioning
confidence: 99%